Hormone replacement therapy and prognosis in ovarian cancer patients - Hein, Alexander; Thiel, Falk; Bayer, Christian M.; Fasching, Peter; Häberle, Lothar; Lux, Michael P.; Renner, Stefan; Jud, Sebastian; Schrauder, Michael G.; Müller, Andreas; Wachter, David; Strehl, Johanna; et al. (European Journal of Cancer Prevention, 2013)
Estrogen exposure has at least a moderate effect on the risk for ovarian cancer, and antiestrogen therapy may be helpful in treating the disease. It is known from breast cancer that previous hormone replacement therapy (HRT) may influence the molecular profile and prognostic behavior of these tumors. The aim of this study was therefore to investigate the influence of previous HRT on the prognosis in a cohort of patients with invasive epithelial ovarian cancer. Among 547 patients who were treated for ovarian malignancies at a single institution from 1995 to 2008, a total of 244 postmenopausal patients with epithelial cancer and under the age of 75 were identified for whom information about HRT before the onset of the disease was available. HRT was correlated with tumor and patient characteristics. Analyses of overall survival and progression-free survival were carried out using Cox proportional hazards models. Age, tumor stage, and resection status correlated significantly with HRT in the univariate analysis. Patients with previous HRT were more likely to have a lower stage, to be younger, and to have optimal debulking. With regard to survival, HRT had a positive effect on overall survival, specifically in the subgroup of patients with optimal debulking. No correlation was seen in relation to progression-free survival. Sex hormone exposure through HRT may influence the behavior of ovarian cancers after the onset of the disease. This study supports the hypothesis that ovarian cancer is a hormonally influenced tumor. © 2012 Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2021-07-19
Keywords: estrogen; hormone replacement therapy; ovarian cancer; pathogenesis; prognosis